2004
DOI: 10.1093/ndt/gfh204
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac work up in primary renal hypokalaemia-hypomagnesaemia (Gitelman syndrome)

Abstract: The QT interval is often prolonged in primary renal hypokalaemia-hypomagnesaemia, confirming that potassium and magnesium depletion tends to prolong the duration of the action potential of the cardiomyocyte. The results of continuous ambulatory electrocardiography, exercise testing and echocardiography are reassuring. Nonetheless, we assume that dangerous cardiac arrhythmias may occur in patients with very severe hypokalaemia, during medication with drugs that prolong the QT interval or in the context of short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 25 publications
2
41
0
2
Order By: Relevance
“…Another study specifically looking at cardiac workup in Gitelman's syndrome, found out that QT interval is often prolonged but 24 hour Holter, treadmill exercise, echocardiographic data was unchanged. 7 Similar changes in QT interval were reported from other study without any documentation of arrhythmia. Magnesium deficiency can potentially result in torsades-de-pointes and cardiomyopathy.…”
Section: Discussionsupporting
confidence: 84%
“…Another study specifically looking at cardiac workup in Gitelman's syndrome, found out that QT interval is often prolonged but 24 hour Holter, treadmill exercise, echocardiographic data was unchanged. 7 Similar changes in QT interval were reported from other study without any documentation of arrhythmia. Magnesium deficiency can potentially result in torsades-de-pointes and cardiomyopathy.…”
Section: Discussionsupporting
confidence: 84%
“…exercise testing failed to detect significant abnormalities of cardiac rhythm in our Gitelman patients [13]. Nonetheless, since both hypokalemia and hypomagnesemia were rather mild in these patients, we presumed [14] that dangerous cardiac arrhythmias may occur in patients with severe hypokalemia (and hypomagnesemia), as indicated by the case of a newborn with profound hypokalemia in the context of the antenatal form of Bartter syndrome, who developed severe cardiac arrhythmias and cardiac arrest [15].…”
mentioning
confidence: 83%
“…Foglia ir kt. išdėstė, kad pirminės inkstų hipokalemijos-hipomagnezemijos metu nustatomi pailgėję QT intervalai, patvirtinantys, kad kalio ir magnio išeikvojimas pailgina kardiomiocito veikimo potencialo trukmę [35]. Magnio deficitas prailgina veikimo potencialo plato fazę.…”
Section: Elektrokardiografiniai Pokyčiaiunclassified